Mapping of Tilapia Lake Virus entry pathways with inhibitors reveals dependence on dynamin activity and cholesterol but not endosomal acidification - Abu Rass, Reem; Kembou-Ringert, Japhette Esther; Zamostiano, Rachel; Eldar, Avi; Ehrlich, Marcelo; Bacharach, Eran (Frontiers in Cell and Developmental Biology, 2022)
Tilapia Lake Virus (TiLV) is an emerging virus lethal to tilapia, which threatens the global tilapia aquaculture with severe implications for food security. TiLV possesses similar features to orthomyxoviruses but is classified in the sole and the monotypic genus Tilapinevirus of the family Amnoonviridae. TiLV enveloped virions encapsidate a genome comprising ten segments of single-stranded, negative RNA. Remarkably, nine of TiLV's ten major proteins lack sequence homology to any known viral or cellular proteins. The mode of TiLV entry into tilapia cells is not known. Following the measurement of the entry window of TiLV (~3 hours), we applied a panel of inhibitors of known regulators of endocytic functions to map the molecular requirements for TiLV entry. We identified productive entry by quantification of TiLV nucleoprotein expression and the generation of infectious particles. Inhibition of dynamin activity with dynasore or dynole, or depletion of cholesterol with methyl-β-cyclodextrin, strongly inhibited TiLV protein synthesis and infectious virion production. Moreover, inhibition of actin cytoskeleton polymerization with latrunculin A or microtubule polymerization with nocodazole within the entry window resulted in partial inhibition of TiLV infection. In contrast, inhibitors of endosomal acidification (NH4Cl, bafilomycin A1, or chloroquine), an inhibitor of clathrin-coated pit assembly (pitstop 2), and erlotinib - an inhibitor of the endocytic Cyclin G-associated kinase (GAK), did not affect TiLV entry. Altogether, these results suggest that TiLV enters via dynamin-mediated endocytosis in a cholesterol-, cytoskeleton-dependent manner, and clathrin-, pH-independent manner. Thus, despite being an orthomyxovirus-like virus, when compared to the prototypical orthomyxovirus (influenza A virus), TiLV shows a distinct set of requirements for entry into cells.